2014
DOI: 10.1007/s12038-014-9452-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender based disruptive selection maintains body size polymorphism in Drosophila melanogaster

Abstract: Darwinian fitness in holometabolous insects like the fruit fly Drosophila melanogaster is reported to be positively correlated with body size. If large individuals in a population have higher fitness, then one would expect directional selection to operate leading to uniformly large individuals. However, size polymorphism persists in nature and needs further probing. We assessed the effect of body size on some of the fitness and fitness-related traits in replicate populations of genotypically large, genotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…The longevity of reproducing female and male F A , F B , F C , F D , and F E flies was assessed in mixed sex cultures (Handa et al 2014). The flies were sorted into vials containing ∼4 mL SM under light diethyl ether anesthetization.…”
Section: Longevity Assay Of Actively Reproducing Progeny (F) Fliesmentioning
confidence: 99%
“…The longevity of reproducing female and male F A , F B , F C , F D , and F E flies was assessed in mixed sex cultures (Handa et al 2014). The flies were sorted into vials containing ∼4 mL SM under light diethyl ether anesthetization.…”
Section: Longevity Assay Of Actively Reproducing Progeny (F) Fliesmentioning
confidence: 99%
“…Although the selected populations are under the physiological trigger to complete development due to higher ecdysone levels throughout L3 38 they can accumulate adequate proteins and lipids to maintain their phenotypic integrity albeit emerge as small adults 13,38 . Despite small size due to curtailed post-critical duration their copulation latency (i.e., time to attain sexual maturity) and copulation duration were unaffected supporting the claim that sexual maturity and copulation duration are speciesspeci c traits 18 . However, copulation latency and duration were affected when Drosophila melanogaster was starved during early adult life 41 .…”
Section: Discussionmentioning
confidence: 61%
“…The differences in the two ndings might be due to diet restriction at different life stages ascertained in the two studies. Two studies in the past have reported decoupling of body size and copulation duration 18,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations